2022
DOI: 10.1186/s12887-022-03284-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of breakfast skipping among children and adolescents: a cross-sectional population level study

Abstract: Background Interventions to promote breakfast consumption are a popular strategy to address early life inequalities. It is important to understand the epidemiology of children and adolescents who skip breakfast so that interventions and policy can be appropriately considered. This study investigated the prevalence of breakfast skipping among a contemporary, population-wide sample of children and adolescents in Australia. Methods Participants were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…However, the same individuals often skipped meals (93%) and did not eat fruits and vegetables (57.4%). These unhealthy eating behaviors are associated with overweight and obesity [ 53 , 54 ]. Furthermore, the dietary habits of adolescents in Zimbabwe requires further investigation within the context of socio-cultural beliefs and the changing food environments [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the same individuals often skipped meals (93%) and did not eat fruits and vegetables (57.4%). These unhealthy eating behaviors are associated with overweight and obesity [ 53 , 54 ]. Furthermore, the dietary habits of adolescents in Zimbabwe requires further investigation within the context of socio-cultural beliefs and the changing food environments [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Binary logistic regression revealed that there were no significant associations between low obesity awareness and nutrition knowledge, physical activity levels, BtC, and BMI. These results were unexpected because of the well-known link between obesity and poor nutrition knowledge and PA [ 54 , 55 ]. Further research is warranted to shed more light on this area.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of a large number of children and adolescents (n = 285 626; aged 2-18 years) across 33 countries suggested around 10%-30% are skipping breakfast, with a higher frequency among adolescents compared to younger children (Monzani et al, 2019). Other research also found skipping breakfast to be more frequent in females and low socio-economic groups compared to males and higher income groups (Coulthard et al, 2017;de la Hunty et al, 2013;Hoyland et al, 2012;Inchley et al, 2020;Sincovich et al, 2022). It has been postulated that the age differential in breakfast skipping may partly reflect the shift in circadian rhythms in adolescence to a later wake/sleep cycle as well as having more agency over their food choices (Coulthard et al, 2017).…”
Section: How Common Is Bre Akfast Sk Ipping In Young People?mentioning
confidence: 99%
“…It has been postulated that the age differential in breakfast skipping may partly reflect the shift in circadian rhythms in adolescence to a later wake/sleep cycle as well as having more agency over their food choices (Coulthard et al., 2017). Other cited reasons for missing breakfast include a lack of time, no enjoyment of breakfast or not feeling hungry in the morning, and weight control, especially in adolescent girls (de la Hunty et al., 2013; Sincovich et al., 2022). In the Spanish DESKcohort study including 7319 adolescents, breakfast skipping was suggested to be around 30% higher in adolescents in the most deprived compared to the least deprived groups (Esquius et al., 2021), and the authors suggested that this may be related in part to lack of access to, or availability of, food.…”
Section: How Common Is Breakfast Skipping In Young People?mentioning
confidence: 99%
“…Skipping breakfast is more frequent among women, later adolescents, those living in single-parent households, and in lower socioeconomic positions [ 6 ]. Breakfast skipping has also been found to be positively correlated with overweight/obesity (OW/OB) and biomarkers of metabolic diseases [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%